Additive genetic and heterotic effects in a 4 × 4 complete diallel cross‐population of Nile tilapia (Oreochromis niloticus, Linnaeus, 1758) reared in different water temperature environments in Northern Vietnam. (17th July 2014) - Thoa, Ngo P; Ninh, Nguyen H; Hoa, Nguyen T; Knibb, Wayne; Diep, Nguyen H; Nguyen, Nguyen H
Abstract: This study aims to estimate the strain additive genetic and heterotic effects on growth and survival in a 4 × 4 complete diallel cross‐population of Nile tilapia. Mass spawning was practised in replicate hapas to simultaneously produce progeny of all crosses for performance testing in three environments (in ponds at 20–30°C, in tanks at 15–20°C and in tanks at 20–25°C). A total of 6735 individually tagged fish were tested over a grow‐out period of 278 days. Statistical analyses were carried out on 5097 body trait records available at harvest. Across the test environments, the NOVIT4 strain exhibited the highest additive genetic values for both growth and survival (19% and 33% above the pure strain mean respectively). The heterosis effect was low and not different from zero for both traits. The ranking of strains with respect to their additive genetic values generally did not change between tank environments (15–20 vs. 20–25°C). The correlations of the additive genetic performance between tank environments were also high (0.84), suggesting that strain by water temperature interaction was likely not biologically important. By contrast, the differences in both performance and survival between pond and tank environments were statistically significant, indicating that this effect should be accounted for in future breeding programmes. The large additive genetic effect among strains coupled with the non‐significant heterotic effects in our study suggest that future breeding programme in this population of Nile tilapia should be based on a wise choice of strain or by exploiting the additive genetic variation through selective breeding.